Induction of biotransformation enzymes by the carcinogenic air-pollutant 3-nitrobenzanthrone in liver, kidney and lung, after intra-tracheal instillation in rats - Mizerovská, Jana; Dračínská, Helena; Frei, Eva; Schmeiser, Heinz; Arlt, Volker M.; Stiborová, Marie (Mutation research. Genetic toxicology and environmental mutagenesis, 2011)
3-Nitrobenzanthrone (3-NBA), a carcinogenic air pollutant, was investigated for its ability to induce cytochrome P450 (CYP) 1A1/2 and NAD(P)H:quinone oxidoreductase (NQO1) in liver, kidney and lung of rats treated by intra-tracheal instillation. The organs used were from a previous study performed to determine the persistence of 3-NBA-derived DNA adducts in target and non-target tissues (Bieler et al., Carcinogenesis 28 (2007) 1117-1121, [22]). NQO1 is the enzyme reducing 3-NBA to N-hydroxy-3-aminobenzanthrone (N-OH-3-ABA) and CYP1A enzymes oxidize a human metabolite of 3-NBA, 3-aminobenzanthrone (3-ABA), to yield the same reactive intermediate. 3-NBA and 3-ABA are both activated to species forming DNA adducts by cytosols and/or microsomes isolated from rat lung, the target organ for 3-NBA carcinogenicity, and from liver and kidney. Each compound generated the same five DNA adducts detectable by 32P-postlabelling. When hepatic cytosols from rats treated with 0.2 or 2mg/kg body weight of 3-NBA were incubated with 3-NBA, DNA adduct formation was 3.2- and 8.6-fold higher, respectively, than in incubations with cytosols from control animals. Likewise, cytosols isolated from lungs and kidneys of rats exposed to 3-NBA more efficiently activated 3-NBA than those of control rats. This increase corresponded to an increase in protein levels and enzymatic activities of NQO1. Incubations of hepatic, pulmonary or renal microsomes of 3-NBA-treated rats with 3-ABA led to an 9.6-fold increase in DNA-adduct formation relative to controls. The highest induction in DNA-adduct levels was found in lung. The stimulation of DNA-adduct formation correlated with expression of CYP1A1/2 induced by the intra-tracheal instillation of 3-NBA. The results demonstrate that 3-NBA induces NQO1 and CYP1A1/2 in livers, lungs and kidneys of rats after intra-tracheal instillation, thereby enhancing its own genotoxic and carcinogenic potential.